2002
DOI: 10.1093/dnares/9.6.199
|View full text |Cite
|
Sign up to set email alerts
|

Development and Mapping of 2240 New SSR Markers for Rice (Oryza sativa L.)

Abstract: A total of 2414 new di-, tri- and tetra-nucleotide non-redundant SSR primer pairs, representing 2240 unique marker loci, have been developed and experimentally validated for rice (Oryza sativa L.). Duplicate primer pairs are reported for 7% (174) of the loci. The majority (92%) of primer pairs were developed in regions flanking perfect repeats > or = 24 bp in length. Using electronic PCR (e-PCR) to align primer pairs against 3284 publicly sequenced rice BAC and PAC clones (representing about 83% of the total r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
850
2
18

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,319 publications
(916 citation statements)
references
References 26 publications
46
850
2
18
Order By: Relevance
“…Further, dense genetic maps are important to prepare contig-based local or genome wide physical maps, for map-based cloning and for genome sequencing projects. Since microsatellite markers are currently preferred over other molecular markers for a variety of reasons, high density microsatellite maps, such as those developed in rice (McCouch et al 2002), maize (Sharopova et al 2002) and wheat (Somers et al 2004), are very useful.…”
Section: Discussionmentioning
confidence: 99%
“…Further, dense genetic maps are important to prepare contig-based local or genome wide physical maps, for map-based cloning and for genome sequencing projects. Since microsatellite markers are currently preferred over other molecular markers for a variety of reasons, high density microsatellite maps, such as those developed in rice (McCouch et al 2002), maize (Sharopova et al 2002) and wheat (Somers et al 2004), are very useful.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty two published drought and salt tolerance linked SSR markers were selected (Akagi et al 1996;Panaud et al 1996;Temnykh et al 2000;McCouch et al 2002) which were reported in different indica rice lines. Detailed information of these markers was collected from Gramene database (www.gramene.org), a freely available comparative web data resource for cereal crops.…”
Section: Marker Selection For Genotypingmentioning
confidence: 99%
“…Some of the SSR primers were taken from Temnykh S et al [10] and McCouch SR [11]. Others were directly designed from the rice genome sequences according to Rice Genome Program (RGP).…”
Section: Ssr Marker Designmentioning
confidence: 99%